If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 80 + -28x = 0 Solving 80 + -28x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-80' to each side of the equation. 80 + -80 + -28x = 0 + -80 Combine like terms: 80 + -80 = 0 0 + -28x = 0 + -80 -28x = 0 + -80 Combine like terms: 0 + -80 = -80 -28x = -80 Divide each side by '-28'. x = 2.857142857 Simplifying x = 2.857142857
| 3x*2=0 | | f(x)=3x+48+1 | | 1.8*1.2= | | sin2(v-180/12)=0.5 | | 80=(2w+6)w | | y=0x+1.35 | | 24-4/5 | | W=Q^(9/10) | | 24-4/5=x | | W=Q^9/10 | | ln(x)=ln(21) | | 85/3x-25=x | | y=-0.07x+1.47 | | 56=(2w+6)w | | 2log(x)-log(7x-1)=0 | | 6v^2-19v+15=0 | | 15-3x=8+4x | | 85/3-25=x | | 85/3-25 | | 234=(2w+8)w | | 85-25/3=x | | Z/4=4 | | Cb+ad=0 | | 5s(13s+8)=0 | | 6-726=6r | | r(r+7)=0 | | 12x-36=-6+18 | | 0=-16x^2-16x+60 | | 4sec^2x-3=0 | | 4x/25=85-x/100 | | 2+3(n+4)=3n+10 | | -13x+-13=13 |